INTERNATIONAL EXPERIENCE OF INCREASING THE ECONOMIC POTENTIAL OF FOOD INDUSTRY (ON THE EXAMPLE OF THE DAIRY INDUSTRY) - A.ZH. Bayguzhinova, (Academic Journal of Physical and Chemical Sciences, 2019)
In all regions of the world, the requirements for the management of dairy farming are increasing, taking into account the need to protect ecosystems. The dairy industry is increasingly moving to farming without the use of fertilizers and pesticides (organic farming) or using them in small quantities (integrated farming). This is due to the growing popularity of whole milk consumption among the population. Growing demand in less developed markets stimulates dairy producers to increase their own production. At the same time, a situation of tightening the struggle for high-quality raw materials (raw milk) with countries - exporters of raw materials. States whose dairy industry is in high demand to achieve a level of product self-sufficiency are investing in the development of production, improving assortment policy, and entering into contracts for the supply of quality raw materials.